A cross-sectional survey to explore healthcare providers’ experiences and attitudes toward HIV pre-exposure prophylaxis for women in family planning centers of Greater Paris - Geoffroy Liegeon; Joseph A. Mason; Eleanor E. Friedman; Myriam Toribio; Sophie Florence; Elena Villalon; Julie Castaneda; Andrés Ramírez Zamudio; Samantha A. Devlin; Jessica P. Ridgway; Amy K. Johnson; Victoria Manda (PLoS ONE, 2026)
Despite representing a disproportionately high percentage of new HIV diagnoses in France annually, women who have migrated from Sub-Saharan Africa (WMSSA) remain underserved by HIV prevention strategies, including Pre-Exposure Prophylaxis (PrEP). This study aimed to understand healthcare providers’ experiences and attitudes toward PrEP delivery to WMSSA within family planning centers (FPCs) of the Paris region in France. We conducted a web-based cross-sectional survey from February to June 2024 to explore the knowledge, attitudes, and experiences of providers in FPCs in Paris and Seine-Saint-Denis (SSD) County. The survey link was emailed to FPC providers via their departmental mailing lists. Of the 284 providers who were contacted, 64 completed the survey (response rate of 23%). Respondents were predominantly women (95%), with a median age of 44 (IQR 35–53) and a median of 17.5 (IQR 10–26) years of professional experience. They worked as physicians (44%), midwives (34%), or nurses (22%), primarily in FPCs within SSD County (77%). All providers had heard of PrEP; 42% had already discussed it with a client; 28% reported PrEP prescriptions being offered in their FPC; and 21% had already prescribed it for a woman. Among participants, 42% had received PrEP training, and 53% rated their overall PrEP knowledge as good or very good. About one-third of providers reported feeling uncomfortable discussing or prescribing PrEP to women. The top three barriers to PrEP implementation were the lack of PrEP awareness among clients (32%), inadequate provider training (21%), and the limited number of PrEP prescribers in FPCs (21%). Providers endorsed multiple interventions to increase PrEP delivery, including PrEP training, educational materials, and policy shifts to broaden prescriber roles. FPC providers in Paris and SSD County have limited experience in delivering PrEP to women. Several facilitators were identified to inform PrEP implementation strategies at the provider, client and structural levels.